The Connectivity of Hadith and Modern Sains: Case Study on Hadith about Pomegranate: Konektifitas Hadis dan Sains Modern: Studi Kasus pada Hadis tentang Delima - Baiq Mira Nurfatihah; Ma'sum Al Anwari, Ahmad Ubaidillah (Jurnal Living Hadis, 2023)
The Prophet through his hadiths taught goodness to his people, both in the realm of attitude, character, worship, and even greater things. In practice, Muslims only implement the prophet's commands to the extent of religious doctrine which considers the prophet to be ma'shum, but they forget the conceptual dimensions that actually support the truth of what the prophet conveyed. This article discusses the connectivity between the hadith of the Prophet SAW and sains through two fundamental questions; first, what is the methodological conceptual relationship between hadith and sains?, and second, to what extent is the truth of hadith seen from a scientific perspective? Both questions are analyzed using descriptive-analytical research methods which will then be compared to find the meeting point. The results found a very close relationship between hadith and sains, where both are built on methodology and are objective. The truth is not just a claim, but the truth is proven through data and facts.